(untitled) (Communications in Computational Physics, 2008)
Long-range electrostatic interactions in proteins/peptides associating to nucleic acids are reflected in the salt-dependence of the binding process. According to the oligocationic binding model, which is based on counterion condensation theory, only the cationic residues of peptides/proteins near the binding interface are assumed to affect the salt dependence in the association of peptides and proteins to nucleic acids. This model has been used to interpret and predict the binding of oligocationic chains–such as oligoarginines/lysines–to nucleic acids, and does an excellent job in these kinds of systems. This simple relationship, which is used to compare or count the number of ionic interactions in protein-nucleic acid complexes, does not hold when acidic residues, i.e. glutamate and aspartate, are incorporated in the protein matrix. Here, we report a combined molecular mechanics (by means of energy-minimization of the structure under the influence of an empirical energy function) and Poisson-Boltzmann (PB) study on the salt-dependence in binding to tRNA of two important enzymes that are involved in the seminal step of peptide formation in the ribosome: Glutamine synthetase (GluRS) and Glutaminyl synthetase (GlnRS) bound to their cognate tRNA. These two proteins are anionic and contain a significant number of acidic residues distributed over the entire protein. Some of these residues are located in the binding interface to tRNA. We computed the salt-dependence in association, SKpred, of these enzyme-tRNA complexes using both the linear and nonlinear solution to the Poisson-Boltzmann Equation (PBE). Our findings demonstrate that the SKpred obtained with the nonlinear PBE is in good agreement with the experimental SKobs, while use of the linear PBE resulted in the SKpred being anomalous. We conclude that electrostatic interactions between the binding partners in these systems are less favorable by means of charge-charge repulsion between negatively charged protein residues and phosphate oxygens in the tRNA backbone but also play a significant role in the association process of proteins to tRNA. Some unfavorable electrostatic interactions are probably compensated by hydrogen-bonds between the carboxylate group of the side chain in the interfacial acidic protein residues and the tRNA backbone. We propose that the low experimentally observed SKobs values for both GlnRS- and GluRS-tRNA depend on the distribution and number of anionic residues that exist in these tRNA synthetases. Our computed electrostatic binding free energies were large and unfavorable due to the Coulombic and de-solvation contribution for the GlnRS-tRNA and GluRS-tRNA complexes, respectively. Thus, low SKobs values may not reflect small contributions from the electrostatic contribution in complex-formation, as is often suggested in the literature. When charges are "turned off" in a computer-experiment, our results indicated that "turning off" acidic residues far from a phosphate group significantly influences SKpred. If cationic residues are "turned off", less impact on SKpred is observed with respect to the distance to the nearest phosphate-group.